Intraoperative radiotherapy for resectable brain metastases: a systematic review and meta-analysis - Dejonckheere, Cas S.; Schneider, Matthias; Potthoff, Anna-Laura; Hamed, Motaz; Scafa, Davide; Zeyen, Thomas; Friker, Lea L.; Grimmer, Molina; Kugel, Fabian; Garbe, Stephan; Radbruch, Alexander; Vatter, Hartmut; et al. (Radiotherapy and oncology, 2025)
Background - In recent years, intraoperative radiotherapy (IORT) with low-energy X-rays is emerging as an alternative to postoperative stereotactic radiotherapy (SRT) of the resection cavity in patients with resectable brain metastases (BMs). - Methods - We performed a systematic review of the MEDLINE, Embase, and Scopus databases, including all original articles on IORT for resectable BMs from 2015 to 2025. Data on safety, local control, and survival outcomes were collected. - Results - Ten records (5 prospective single-arm trials) were included, representing 261 patients (49 % lung primary) with a median follow-up (range) of 14 (0-79) months. 77 % of patients had a solitary BM at the time of surgery and IORT. The median applicator size was 2.0 cm and the median prescribed dose (range) 22.3 (20-30) Gy. The 1-year local control rate was 93 % and the 1-year distant brain control rate 48 %. Median overall survival was 19 months. Only 6 % of patients developed leptomeningeal disease and the cumulative rate of radiation necrosis was 2.6 % (grade 1 in 56 % of cases). The median time to next treatment beyond BM therapy (range) was 31 (1-136) days. This was significantly shorter compared to SRT control collectives. - Conclusions - IORT for patients with BMs has a favorable toxicity profile and yields excellent local control. A potential advantage is the rapid completion of interdisciplinary BM treatment, allowing a swift transition to subsequent cancer treatments. A planned registry and a prospective randomized phase 3 trial will establish the preferred radiotherapy modality in the context of resectable BMs.
Online verfügbar: 8. September 2025, Artikelversion: 12. September 2025
Gesehen am 04.12.2025